An Antihyperlipidemic Agents Review for Atherosclerosis Treatment - Rutuja Talekar; Nanasaheb Gorade; Sachin Jadhav; Pratiksha Chormage; Shivani Gadekar; Swati H.Tarkase; Dr.Gajanan Sanap (Asian Journal of Pharmaceutical Research and Development, 2026)
Elevated levels of one or more plasma lipids, including triglycerides, cholesterol, cholesterol esters, phospholipids, and/or plasma lipoproteins, including very low-density lipoprotein and decreased levels of high-density lipoprotein are indicative of a medical condition called hyperlipidemia. This elevation in plasma lipids is one of the primary risk factors for cardiovascular diseases.Statins and fibrates remain the main antihyperlipidemic drugs for the treatment of elevated plasma cholesterol and triglycerides, respectively, at the cost of major negative effects on the liver and muscles. Hyperlipidemia is the main risk factor for coronary heart disease.